2016
DOI: 10.1016/j.jnutbio.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-tocotrienol acts as a BH3 mimetic to induce apoptosis in neuroblastoma SH-SY5Y cells

Abstract: Bcl-2 family proteins are crucial regulators of apoptosis. Both pro- and antiapoptotic members exist, and overexpression of the latter facilitates evasion of apoptosis in many cancer types. Bcl-2 homology domain 3 (BH3) mimetics are small molecule inhibitors of antiapoptotic Bcl-2 family members, and these inhibitors are promising anticancer agents. In this study, we report that gamma-tocotrienol (γT3), an isomer of vitamin E, can inhibit Bcl-2 to induce apoptosis. We demonstrate that γT3 induces cell death in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Secondly, T3 may act differently when exist in combination with other compounds due to drug interaction. For instance, γT3 interferes with the generation of ROS by BSO which is beneficial for cancer cell death [399].…”
Section: Effects Of Tocotrienol On Cancersmentioning
confidence: 99%
“…Secondly, T3 may act differently when exist in combination with other compounds due to drug interaction. For instance, γT3 interferes with the generation of ROS by BSO which is beneficial for cancer cell death [399].…”
Section: Effects Of Tocotrienol On Cancersmentioning
confidence: 99%
“…The TRMC consisted of α-tocotrienol, β-tocotrienol, and γ-tocotrienol and the δ-tocotrienol isomers. Some studies have shown that γ-tocotrienol induced apoptosis in neuroblastoma SH-SY5Y cells 47 and human gastric cancer cells. 48 In our previous study, we clearly showed that delta-tocotrienol induced apoptosis in NSCLC in a dose-and time-dependent manner at 10-30 µM concentrations.…”
mentioning
confidence: 99%
“…Tocotrienols have cytotoxic properties against cancer cells in culture (8387). Many molecular mechanisms have been proposed, including induction of the mitochondrial apoptosis pathway (88,89), altered sphingolipid metabolism (90), endoplasmic reticulum stress (91), inhibition of telomerase (92), inhibition of signaling pathways involved in cytoskeletal organization (93) induction of cyclin dependent kinase inhibitors p21 and p27 (94), inhibition of canonical Wnt signaling (95), and modification of the Ras-ERK pathway (96).…”
Section: Tocotrienols Have Anti-cancer Propertiesmentioning
confidence: 99%